SELEKSI BEBERAPA PROGENI HASIL PERSILANGAN PADI GOGO (Oryza sativa L) BERDASARKAN KARAKTER PERTUMBUHAN TANAMAN - Sadimantara, Gusti Ray; Widarsih, Asih; Muhidin, Muhidin (Jurnal Agroteknos, 2013)
Rice is an important food crop in the world, exceeding potatoes, corn, wheat and other cereals. The experiment was conducted to study differences in the growth characters of some progenies from the crosses of upland rice and to know the cross combinations which produced the best growth characters. The research treatment was seven progenies from crosses of upland rice. Seven progenies of the rice grown in the field experiment were evaluated based on morphological characters, especially rice stems and leaves. Based on the stem color and the color of the sheath, there were two groups consisted of F2 plants population of progeny A (33/Wagamba (1)), E (Wagamba/33), and F (33/Wagamba (3)) with the color purple midrib purple stem and base. In the second group contained of the F2 plant population of progeny B ( 33/Wagamba (2)), C (Cegelius/Wangkoito (1)), D (Cegelius/Wangkoito (2)), and G (33/Wagamba (4)) with the base of the stem and sheath color were green. The progeny A (33/Wagamba (1)) and progeny E (Wagamba/33) were the best progeny because it had several advantages such as growth form upright, erect leafs, plant height, number of tillers, and dark green leaves. Keywords: growth character, crosses, upland rice, progeny, selection.